(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
One of the most marginalized communities in India are the tribal communities. India’s population include nearly one hundred million tribal people. Tribal community in India has been most vulnerable community in the in equal, domination and exploitation ridden society. They are on the breadline of their socio-economic and political rights. As the United Nations Declaration of Human Rights has given the rights of indigenous people, the Indian constitution also has given several provision for rights of tribal communities regarding the social, economics, and education, culture, political and service. This paper highlight the provision of tribal rights that was enshrines in the Indian constitution.